Linking murine resistance to secondary cystic echinococcosis with antibody responses targeting Echinococcus granulosus tegumental antigens - Miles, Sebastián; Magnone, Javier; Cyrklaff, Marek; Arbildi, Paula; Frischknecht, Friedrich; Dematteis, Sylvia; Mourglia-Ettlin, Gustavo (Immunobiology, 2020)
Successful establishment of a parasite infection depends partially on the host intrinsic susceptibility to the pathogen. In cystic echinococcosis (CE), a zoonotic disease caused by the cestode parasite Echinococcus granulosus, the infection outcome in the murine model of secondary CE varies according to the mouse strain used. In this regard, intrinsic differences in susceptibility to the infection were previously reported for Balb/c and C57Bl/6 mice, being C57Bl/6 animals less permissive to secondary CE. Induction of parasite-specific antibodies has been suggested to play relevant roles in such susceptibility/resistance phenomena. Here, we report an in deep comparison of antibody responses induced in both mouse strains. Firstly, only C57Bl/6 mice were shown to induce specific-antibodies with efficient anti-parasite activities during early secondary CE. Then, through ImmunoTEM and Serological Proteome Analysis (SERPA), an evaluation of specific antibody responses targeting parasite tegumental antigens was performed. Both strategies showed that infected C57Bl/6 mice -unlike Balb/c animals- narrowed their IgG recognition repertoire against tegumental antigens, targeting fewer but potentially more relevant parasite components. In this sense, tegumental antigens recognition between Balb/c and C57Bl/6 mice, either by natural and/or induced antibodies, was analyzed through SERPA and MALDI-TOF/TOF studies. A total of 13 differentially recognized proteins (DRPs) uniquely targeted by antibodies from C57Bl/6 mice were successfully identified, wherein a subset of 7 DRPs were only recognized by infection-induced antibodies, suggesting their potential as natural protective antigens. In this regard, immunoinformatic analyses showed that such DRPs exhibited higher numbers of possible T cell epitopes towards the H-2-IA(b) haplotype, which is present in C57Bl/6 mice but absent in Balb/c animals. In summary, our results showed that the genetic predisposition to generate better T-dependent antibody responses against particular tegumental antigens might be a key factor influencing host susceptibility in the murine model of secondary CE.
Gesehen am 09.07.2020